Atypical primary varicella rash: Systematic literature review. (27th February 2022) - Mazzara, Calogero; Milani, Gregorio Paolo; Lava, Sebastiano A. G.; Bianchetti, Mario Giovanni; Gualco, Gianluca; Simonetti, Giacomo D.; Camozzi, Pietro; Kottanattu, Lisa
Abstract: Aim: In previously healthy subjects, primary varicella presents with a distinctive vesicular rash that is more intense on the trunk and head than on the extremities. However, an atypical presentation may occasionally develop. We aimed at systematically assessing the characteristics of cases affected by atypical primary varicella rash. Methods: The United States National Library of Medicine, Excerpta Medica and Web of Science databases were reviewed, without date or language restrictions. Articles were eligible if reporting previously healthy and immunocompetent subjects with a primary varicella rash (i.e., a photo‐localised primary varicella or skin inflammation‐associated primary varicella). Results: Thirty‐eight reports providing information on 59 cases of atypical primary varicella were identified. Twenty‐four cases (median 8.5 years of age, 19 females) were photo‐localised and 35 (median 4.8 years of age, 15 females) were associated with pre‐existing skin inflammation (including cast occlusion, diaper irritation, operative sites, burns, insect bites, vaccinations or pre‐existing skin disease). The skin rash was monomorphic and without a "starry sky" appearance. Conclusion: Primary varicella may have a modified presentation in areas of irritation such as sun exposure or pre‐existing inflammation. There is a need for a wider awareness of these modulators of varicella rash.